Toxicity Estimation of Graphene Nanoparticles in Mus MusculusUsing Multiple Biomarkers - Aqsa Fayyaz; Tayyaba Ali; Farkhanda Asad; Farhat Jabeen (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Graphene, a strong, super elastic, conductive, and crystalline carbon allotrope, is used in gene and drug delivery, osteon and dental implants, tissue grafting, biosensing, bioimaging, and photothermal therapies, etc. In the current study we evaluated the mutagenic potential of graphene by using Ames tests. Genetic damage and Hemolytic potential was also tested using comet assay and hemolysis assay. Male albino mice (n=66) were randomly selected, 5ml fresh blood from two of them were drawn for Hemolysis assay, and the remaining mice were divided into four groups; three treatment groups (dosages of 110mg/Kg, 220mg/kg, and 330mg/kg) and a control group. After treatment, blood was drawn for comet assay. Each group was again subdivided into three sub groups which were treated with L ascorbic acid (0.025 mg), retinol (0.03 mg) and no treatment for 15 days, and at 16th day same procedure was utilized for sample collection for comet assay. Data were recorded in CASP software and analyzed by using one-way ANOVA. The results of the Ames test indicate graphene is non-mutagenic, with a mutagenicity index less than 2 and 1.8 for TA98 and TA100 strains respectively. Dose dependent increase in hemolysis rate was also found in graphene because it can rupture the membrane of red blood cells (erythrocytes). Comet assay results showed Short-term oral exposure to graphene in male albino mice causes DNA damage, which can be repaired if exposure is ceased and some nutritional supplements if added.